Implementation of the PAIKEM Model to Improve Student Learning Creativity in Aqidah and Moral Learning at MTS Negeri 1 Aceh Singkil - Mawarni; Nasir, Muhammad (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' learning creativity in Islamic religious education learning using the PAIKEM method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the PAIKEM method can improve students' learning creativity in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of the PAIKEM method can be used as an alternative to improve students' learning creativity in Islamic religious education learning.